Comparative Genomics of the Ectomycorrhizal Sister Species Rhizopogon vinicolor and Rhizopogon vesiculosus (Basidiomycota: Boletales) Reveals a Divergence of the Mating Type B Locus - Alija Bajro Mujic; Alan Kuo; Andrew Tritt; Anna Lipzen; Cindy Chen; Jenifer Johnson; Aditi Sharma; Kerrie Barry; Igor V. Grigoriev; Joseph W. Spatafora (G3: Genes, Genomes, Genetics, 2017)
Divergence of breeding system plays an important role in fungal speciation. Ectomycorrhizal fungi, however, pose a challenge for the study of reproductive biology because most cannot be mated under laboratory conditions. To overcome this barrier, we sequenced the draft genomes of the ectomycorrhizal sister species Rhizopogon vinicolor Smith and Zeller and R. vesiculosus Smith and Zeller (Basidiomycota, Boletales)—the first genomes available for Basidiomycota truffles—and characterized gene content and organization surrounding their mating type loci. Both species possess a pair of homeodomain transcription factor homologs at the mating type A-locus as well as pheromone receptor and pheromone precursor homologs at the mating type B-locus. Comparison of Rhizopogon genomes with genomes from Boletales, Agaricales, and Polyporales revealed synteny of the A-locus region within Boletales, but several genomic rearrangements across orders. Our findings suggest correlation between gene content at the B-locus region and breeding system in Boletales with tetrapolar species possessing more diverse gene content than bipolar species. Rhizopogon vinicolor possesses a greater number of B-locus pheromone receptor and precursor genes than R. vesiculosus, as well as a pair of isoprenyl cysteine methyltransferase genes flanking the B-locus compared to a single copy in R. vesiculosus. Examination of dikaryotic single nucleotide polymorphisms within genomes revealed greater heterozygosity in R. vinicolor, consistent with increased rates of outcrossing. Both species possess the components of a heterothallic breeding system with R. vinicolor possessing a B-locus region structure consistent with tetrapolar Boletales and R. vesiculosus possessing a B-locus region structure intermediate between bipolar and tetrapolar Boletales.